Forest, resources and people in Bulungan: elements for a history of settlement, trade and social dynamics in Borneo, 1880-2000 - Sellato, B. (Center for International Forestry Research, 2001)
Bulungan regency is the northern part of the province of East Kalimantan, Indonesia. In the course of the last decade, Kalimantan's or Borneo's hinterland has been the target of unprecedented non-timber forest products (NTFP) collecting activity. More intensive NTFP use has contributed to unsustainable extractive practices and environmental damage and to deep social and political disruption. This book examines northern East Kalimantan's trade networks. The historical scope extends from about 1880 to present and primarily focus on Long Pujungan and Malinau districts. Thematically, the study is on institutions and land and forest use patterns, and their changes with emphasis on social and economic features. It explains regional patterns in the light of past relationships between tribal interior groups and trading coastal polities and seeks to understand both the economic contribution of NTFPs and the institutions controlling their use. It offers some broad ideas that should prove useful in understanding how the past has shaped the present and how the present socio-economic situation owes many of its specific features to past patterns and events.